Pedelection. Verlagerungs- und Klimaeffekte durch Pedelec-Nutzung im Individualverkehr. Endbericht. - (:unkn) unknown (My University, 2015)
Sales rates of electric bicycles have grown rapidly over the last ten years. So far, there are hardly any reliable investigations about everyday usage profiles, shifting effects and potentials as well as use and non-use motives of German pedelec users. An assessment of the significance of pedelecs for achieving climate and energy policy guidelines from the "National Development Plan for Electric Mobility" has not been possible so far. The project "Pedelection" closes this research gap. Pedelec users who purchased their electric bike on their own were investigated within the project. For this purpose, 70 field test participants were selected in four key regions and equipped with data loggers to record driving and loading data. These driving and loading parameters were recorded by the participants on at least one contiguous week per season. Up to 312 additional pedelec users in Germany took part in the complemental online surveys. The participants' average age is 55.6 years (field test and online participants). The proportion of women is 29.7%. 83.8% are in possession of a pedelec 25. The speed version of the pedelec, which supports pedaling up to 45 km/h is used by 9.7%. All participants documented their mobility behavior with the help of trip protocols (for all trips, not just pedelec) for one week within each season. In addition, they answered questions about attitudes and pedelec usage patterns - the field test participants verbally, the online participants as part of the online surveys. From spring 2013 until summer 2014, the participants documented an overall total of 14,768 routes and 297,335 kilometers - including 6,805 trips and 77,852 km in use of the pedelec. In addition, the database includes 124 hours of audio interviews with the field test participants as well as 1698 driving and 472 charging records. Only 20% of participants use their pedelec exclusively for leisure and holiday trips, while about 80% use it as a full mean of transport for commuting and other everyday trips. 70% of pedelec trips were completed from April to September, winter use thus was considerably lower. An important focus of the study is the modal shift induced by pedelecs: 41% of the pedelec trips and 45% of the pedelec kilometers replaced car trips, while 38% of the pedelec trips and 32% of the kilometers were completed with a conventional bicycle before buying a pedelec. The participants only marginally substituted other means of transport. Since participants consumed on average 0.73 kWh/100 km, the manufacturing process of the pedelec makes the largest contribution towards climate impacts associated with pedelec use. The most significant climate advantage arises by shifting from cars to the pedelec; such shift saves almost 150 g greenhouse gas emissions per kilometer. By 2030, a greenhouse gas reduction effect of 1.1 to 1.5 million tons could be achieved by an increasing proportion of up to 35% of pedelecs in the bicycle market. The minimization of climate relevant emissions through pedelec usage is especially large where frequent or long distance car trips are replaced by using a pedelec. This is the case particularly for the commuter traffic, where up to 80 million passenger-kilometers could be substituted through the usage of pedelecs on distances up to 15 kilometers. Modal shift potentials should be enhanced by creating or improving the conditions for the daily usage of pedelecs. Against the background of the study such improvements of conditions can be achieved particularly in the following areas: modification of legal requirements, improving bicycle infrastructure, optimizing the handling of the batteries, further technical development of pedelecs, creating incentives for specific addressees and further research in the two-wheel area
Keywords: Individualverkehr; Fahrradverkehr; Forschung; Untersuchung; Pedelec; E-Bike; Elektrofahrrad; Fahrradnutzung; Handlungsempfehlung